2019
DOI: 10.1038/s41467-019-11240-7
|View full text |Cite
|
Sign up to set email alerts
|

Co-option of neurotransmitter signaling for inter-organismal communication in C. elegans

Abstract: Biogenic amine neurotransmitters play a central role in metazoan biology, and both their chemical structures and cognate receptors are evolutionarily conserved. Their primary roles are in cell-to-cell signaling, as biogenic amines are not normally recruited for communication between separate individuals. Here, we show that in the nematode C. elegans , a neurotransmitter-sensing G protein-coupled receptor, TYRA-2, is required for avoidance responses to osas#9, an ascaroside pheromone that… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 71 publications
0
33
0
Order By: Relevance
“…As a dauer-inducing cue, ascaroside pheromones act as a population density indicator to regulate growth in the early larval developmental stage: high pheromone concentrations cause animals to enter into an alternative non-aging, stressresistant, and developmentally arrested dauer larval stage (Butcher et al, 2007;Butcher et al, 2009;Golden & Riddle, 1982, 1984Jeong et al, 2005;Pungaliya et al, 2009;Srinivasan et al, 2008) (Table 1). Subsequently, over a dozen research groups have shown that ascaroside pheromones play additional roles in several behaviors, including genderspecific attraction and repulsion, aggregation, and foraging (Artyukhin et al, 2013;Chute et al, 2019;Fagan et al, 2018;Greene, Dobosiewicz, Butcher, McGrath, & Bargmann, 1. Jeong et al, 2005;2.…”
Section: Ascaroside Pheromonesmentioning
confidence: 99%
See 3 more Smart Citations
“…As a dauer-inducing cue, ascaroside pheromones act as a population density indicator to regulate growth in the early larval developmental stage: high pheromone concentrations cause animals to enter into an alternative non-aging, stressresistant, and developmentally arrested dauer larval stage (Butcher et al, 2007;Butcher et al, 2009;Golden & Riddle, 1982, 1984Jeong et al, 2005;Pungaliya et al, 2009;Srinivasan et al, 2008) (Table 1). Subsequently, over a dozen research groups have shown that ascaroside pheromones play additional roles in several behaviors, including genderspecific attraction and repulsion, aggregation, and foraging (Artyukhin et al, 2013;Chute et al, 2019;Fagan et al, 2018;Greene, Dobosiewicz, Butcher, McGrath, & Bargmann, 1. Jeong et al, 2005;2.…”
Section: Ascaroside Pheromonesmentioning
confidence: 99%
“…In addition to ascr#3, osas#9 ascaroside was characterized as a single pheromone component which causes avoidance behavior in wild-type hermaphrodites (Artyukhin et al, 2013;Chute et al, 2019). osas#9 is an interesting ascaroside since its side chain is derived from the neurotransmitter octopamine and it is produced mainly by starved young L1 larvae (Artyukhin et al, 2013).…”
Section: Avoidance Behavior To Other Ascarosidesmentioning
confidence: 99%
See 2 more Smart Citations
“…We also observed an effect on octanol modulation in tyra2 TA receptor mutants, primarily due to decreased octanol avoidance upon growth on OP50 (4.3 ± 0.25s for tyra2 vs. 2.9 ± 0.13s for WT). TYRA-2 has recently been shown to mediate responses to an OA-linked pheromone 36 , although the reason for the observed effect in OP50-grown animals is currently unclear. Expression of octr1 cDNA in the ASH/ASI sensory neurons restored octanol modulation (Fig.…”
mentioning
confidence: 99%